2024
DOI: 10.1021/acs.orglett.4c01200
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Three-Component Coupling of Cyclopropenones via Sequential C–C Bond Activation and Allylation

Zhou Zhang,
Fei-Fei Liang,
Shu-Lin Zhang
et al.

Abstract: A novel Pd-catalyzed three-component domino reaction for the stereoselective synthesis of highly functionalized allyl cinnamates has been developed. In this protocol, a sequential process of C–C bond activation and intermolecular allylic substitution was well-organized. The key for this transformation is the in situ generated hydrolysis product of cyclopropenone, which triggered a new reaction with vinylethylene carbonates. The reaction mechanism was investigated, demonstrating the high stereoselectivity and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Previously, we observed that 2-methyl-3-phenylcyclopropenone exhibited excellent regioselectivity in coupling reactions . We hypothesized that the C­(phenyl)–C­(O) bond may be easier to cleave than the C­(methyl)–C­(O) bond.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we observed that 2-methyl-3-phenylcyclopropenone exhibited excellent regioselectivity in coupling reactions . We hypothesized that the C­(phenyl)–C­(O) bond may be easier to cleave than the C­(methyl)–C­(O) bond.…”
mentioning
confidence: 99%
“…Cyclopropenones, the smallest “Hückel aromatic” compounds, have demonstrated their exceptional suitability as candidates for ring-strain-driven C–C bond cleavage, serving as a versatile C 3 synthon for the construction of diverse important molecules . In this context, a number of valuable transformations have been successfully developed, including metal-catalyzed oxidative addition of cyclopropenones and β-carbon elimination reactions (Scheme a). , However, the regioselectivity of unsymmetric cyclopropenones has been challenging in most of the transformations, limiting their synthetic utility. Recently, Prescher’s group developed a PPh 3 -catalyzed method for synthesizing butenolides from hydroxymethylcyclopropenones (Scheme b) .…”
mentioning
confidence: 99%